Endless Shout. - Elms, Anthony; Institute of Contemporary Art. University of Pennsylvania, Philadelphia (Los Angeles : Inventory Press, 2019)
Masaoka, Miya ; Lewis, George ; Ensemble Pamplemousse ; Jones, Jennie C. ; Ewart, Douglas ; Whitson, Ni'ja ; SHWABADA The Music of Ndikho Xaba, dr. Nhlanhla Masondo ; de Nieves, Raúl ; Dibeler, Jake ; Vangrin, Whitney ; Somos Monstros ; HARIBO ; Gaines, Charles ; Moten, Fred ; Harris, Theodore ; Crawley, Ashon ; Oliver, Cynthia ; Houston-Jones, Ishmael ; Holland, Fred ; jumatatu m.poe ; taisha paggett, Meena Murugesan ; The Otolith Group ; travis ; Joshua Abrams & Natural Information Society ; Ending ; Elms, Anthony ; Sadao, Amy ; Smith, Wadada Leo
Endless Shout, Institute of Contemporary Art, University of Pennsylvania, Philadelphia, September 14, 2016 - March 19, 2017
boek